Research on Plagiarism in India during 2002-2016 : A Bibliometric Analysis - Chauhan, Suresh Kumar (DESIDOC Journal of Library & Information Technology, 2018)
The issues of plagiarism have been mushrooming more rapidly around the globe. India is also not spared from plagiarism and related issues. Various researchers and academicians have raised their concern on rapidly growing cases of plagiarism. In this study, an analysis was made to identify the average growth of publications written on plagiarism by Indian authors, the degree of author collaboration, most impactful sources for publishing on plagiarism. The data for the period of 2002 – 2016 were extracted from Scopus by executing a query on ‘Plagiarism’ term. In total 385 publications were found and computed. Average citations per publications of 4.01 for the period, 2007-11 was found high as compared to two other block periods of the study whereas block period 2002-06 was witnessed 49.53 per cent annual growth rate. The Single authored publications prevailed more (34.55 per cent) which interestingly also achieved 50.38 per cent of the cited rate. It was also observed that the degree of multi-authored collaboration has been improving with every passing year.